2012
DOI: 10.1111/j.1574-6968.2012.02570.x
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of two Lactobacillus strains with potential probiotic properties

Abstract: Aflatoxin (highly toxic and carcinogenic secondary metabolites produced by fingi) contamination is a serious problem worldwide. Modern agriculture and animal production systems need to use high‐quality and mycotoxin‐free feedstuffs. The use of microorganisms to preserve food has gained importance in recent years due to the demand for reduced use of chemical preservatives by consumers. Lactic acid bacteria are known to produce various antimicrobial compounds that are considered to be important in the biopreserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 21 publications
(33 reference statements)
4
51
0
2
Order By: Relevance
“…flavus producing aflatoxin was investigated with four methods, in the case of seven isolated LAB (Fguiri et al, ). In addition, Gerbaldo et al (), confirmed that Lactobacillus rhamnosus L60 and Lactobacillus fermentum L23 are the most producing of secondary metabolites, such as organic acids, bacteriocins, and hydrogen peroxide. The antifungal activity of these strains inhibited completely the fungal growth of all aflatoxicogenic strains assayed.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…flavus producing aflatoxin was investigated with four methods, in the case of seven isolated LAB (Fguiri et al, ). In addition, Gerbaldo et al (), confirmed that Lactobacillus rhamnosus L60 and Lactobacillus fermentum L23 are the most producing of secondary metabolites, such as organic acids, bacteriocins, and hydrogen peroxide. The antifungal activity of these strains inhibited completely the fungal growth of all aflatoxicogenic strains assayed.…”
Section: Resultsmentioning
confidence: 93%
“…The development of isolates on MRS medium gives colonies of various shapes, sizes, and colors (Figure 1). Several studies demonstrate that the research of LAB from fermented milk have an important role in the field of bio-preservation (Fguiri, Ziadi, Rekaya, Arroum, & Khorchani, 2017;Gerbaldo, Barberis, Pascual, Dalcero, & Barberis, 2012;Samaneh, Mohammad, Giti, & Mohammad, 2016). In addition, the MRS is considered as an ideal medium for the growth of LAB through its richness on different nutrient (De Man et al, 1960).…”
Section: Isolation and Purification Of Lactic Bacteriamentioning
confidence: 99%
“…These results suggest that E. faecium could produce some inhibitory metabolites of the AFB 1 production; on the other hand the competence for essential compound by AFs production must also be considered. Recently, Gerbaldo et al [27] found that two Lactobacillus spp. producers of secondary active metabolites completely inhibited the fungal growth of all aflatoxigenic strains assayed; and AFB 1 production was reduced significantly (95.7 to 100%).…”
Section: Discussionmentioning
confidence: 98%
“…and Enterococcus spp., among others, produce antimicrobial compounds that are important in the bio-preservation of foods and feeds. [25][26][27] LAB have been widely used in food and are "generally regarded as safe" organisms (GRAS). They are used in commercial applications to improve the shelf life of fermented products and to reduce potential health hazards associated with bacteria and mycotoxins.…”
Section: Introductionmentioning
confidence: 99%
“…Two probiotic strains, Lactobacillus rhamnosus L60 and Lactobacillus fermentum L23, were able to inhibit the growth of Aspergillus flavus strains and levels of aflatoxin B1 produced by them (Gerbaldo et al . ). Belguesmia et al .…”
Section: Introductionmentioning
confidence: 97%